Let Us Talk: Lived Experiences In Supporting The Education of Children Affected by Traumatic Grief - Dam-VandeKuyt, Krista (Université d'Ottawa / University of Ottawa, 2022)
This narrative inquiry study collected stories from parents and teachers to build a deep understanding of the lived experiences of raising or teaching children affected by traumatic grief. Research shows that children who experience adversity or loss as trauma, including childhood traumatic grief, may experience long- term disruptions to executive functions and present learning, behavioural and social challenges within school settings. Current research indicates that the adoption of trauma-informed care practices within schools can successfully support students who have experienced trauma and/or childhood traumatic grief. In particular, the development of strong family-school collaboration, understood recently as a form of working alliance, is key in effectively supporting students experiencing mental health issues, including childhood traumatic grief. Using a narrative inquiry approach, this study shares the stories of three women, a mother, a teacher by profession, and a mother who is a teacher by profession, to develop deep understanding of what is being experienced in supporting children affected by childhood traumatic stress and grief. The findings from this study affirmed the need for increased understanding and awareness of the ways that trauma can impact the education of children affected by trauma. The findings also confirmed that insecure attachments can be mitigated with consistent and attuned care. To do this effectively as educators, there is need for increased resources and supports within the schools. This study confirmed the need for increased collaboration to develop strong relationships between students, parents and teachers. The need for collaboration is essential for the successful support of students struggling with the affects of trauma and these findings affirm current conversations on the importance of trauma-informed approaches, relational schools and working alliances.
Keywords: trauma-informed teaching practices; traumatic grief; working alliance; family-school collaboration; grieving children; attachment theory